Enhancing Self-Efficacy in Professional Communication: A Systematic Review of English for Occupational Purposes in EFL Contexts - Ibhar, Muhalida Zia; Hadriana, Hadriana; Supriusman, Supriusman; Suanto, Elfis (UICELE, 2026)
English for Occupational Purposes (EOP) is becoming increasingly important as the global workplace demands that employees perform complex communication tasks in English. However, many learners who possess adequate linguistic competence still experience difficulties in professional communication, indicating that psychological factors, particularly self-efficacy, may influence their performance. This systematic review synthesizes empirical research published between 2011 and 2025 to examine how EOP instruction contributes to the development of self-efficacy among learners in English as a Foreign Language (EFL) contexts. A PRISMA-guided systematic search was conducted in Scopus, Web of Science, and Google Scholar. A total of 21 empirical studies met the inclusion criteria, covering EOP, ESP, speaking self-efficacy, and workplace-oriented communication instruction. Data extraction, quality assessment using the JBI tool, and thematic synthesis were performed. Three major themes emerged: (1) authentic professional tasks create powerful mastery experiences that enhance self-efficacy; (2) there is a significant measurement gap due to the lack of validated EOP-specific self-efficacy instruments; and (3) pedagogical innovations such as project-based learning, e-portfolios, LMS-supported training, and structured feedback consistently strengthen learners’ self-confidence. Cultural influences and communication anxiety also shape self-efficacy. EOP should be conceptualized as a performance-oriented and psychologically informed learning model. Strengthening learners’ self-efficacy requires authentic task design, effective feedback systems, and improved measurement instruments. Future studies should adopt longitudinal, domain-specific, and technology-supported research designs.